ZnO Nanowire‐Based Early Detection of SARS‐CoV‐2 Antibody Responses in Asymptomatic Patients with COVID‐19 (Adv. Mater. Interfaces 14/2022). Issue 14 (13th May 2022) - Kim, Jung; Lee, Sung Kyun; Lee, Jong‐Hwan; Kim, Hye‐Yeon; Kim, Nam Hoon; Lee, Chang Hoon; Lee, Chang‐Seop; Kim, Hong Gi
Abstract : ZnO Nanowire Microplate for COVID‐19 Antibody Responses In article number 2102046, Jung Kim, Chang‐Seop Lee, Hong Gi Kim, and co‐workers report the development of ZnO nanowire‐fabricated microplate by a modified hydrothermal synthesis method for early detection of SARS‐CoV‐2 antibody response in asymptomatic patients with COVID‐19 as well as symptomatic patients.